Menerima âKepengaturanâ Negara, Membayangkan Kemakmuran: Etnografi Tentang Pemukiman dan Perubahan Sosial Orang Suku Laut di Pulau Bertam, Kepulauan Riau - , Khidir Marsanto Prawirosusanto, Prof Dr. Heddy Shri Ahimsa Putra, M.A., M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis discusses the reasons why the nomadic sea tribe, Orang Laut, in Riau Islands Province, Indonesia, accepted state governmentality (Foucault 1991) by choosing to live in a land settlement offered by a Resettlement Program in the mid-1980s. In the age of nation-states, the Indonesian government characterised the Orang Laut as an 'isolated and impoverished community', and took it upon itself to improve the community's welfare. The Resettlement Program has had many negative repercussions for the Sea Nomads' everyday lives. Considering these, it only becomes natural to ask why the nomads chose life as land dwellers instead of returning to boat-dwelling and retaining their sea tribe identities. In which ways did their perceptions of the space of boat-dwellers transform so as to adapt to the life of land dwellers? In this Indonesian case study, the answer lies in the implications of the community's political choices to acquire \"new identities\": as Orang Bertam. This identities redefinition demonstrated how in relation to their clan association, transformation of the Sea nomads' perception of space as boat-dwellers to one of land-dwellers is quite different from the original government design. They no longer maintain Batin as their traditional leader based on his inherent advantages. Furthermore, to live on land means that they will continue to gain benefits from their \"new identity\" as poor fishermen in the form of Resettlement Program aids.